Rubberised concrete refinement by cement substitution and rubber particle pretreatment - Polydorou, Thomaida; Neocleous, Kyriacos; Koutsokeras, Loukas E.; Constantinides, Georgios; Kyriakides, Nicholas; Pilakoutas, Kypros; Hadjimitsis, Diofantos G. (My University, 2019)
Re-use of End-of-life tyre components into concrete is a viable solution to the environmental issue of tyre waste that can result in promising, high added value concrete applications. End-of-life tyre particles are added to conventional concrete by replacement of a percentage of its aggregate content, improving concrete deformability. The material is currently in the initial stages of research for structural applications, with weakness observed over the interfacial transition zone between the rubber and cement paste. This paper examines the potential of cement substitution by a combination of micro and nanoscale silica particles as well as the effect of rubber pre-treatment by coating with a Diabase quarry dust slurry for surface modification; aiming to refine the rubber/cement paste interface in rubberised concrete, thus improving its compressive strength and consequently structural performance. The effectiveness of cement substitution and rubber treatment methods is measured by comparison of the samples compressive strength at 7 and 28 days and detected in microscopic observations of hardened rubberised concrete samples. It is indicated the rubber pre coating method investigated is a promising procedure, proven to be effective in reducing the porosity at the rubber-cement paste interface and increasing the 28-day concrete compressive strength more than twice.
Keywords: Circular economy; Cement substitution; Rubberised concrete; Fibre reinforcement; End-of-life tyres